Epidemiological determinants of obesity in adolescent population Maharashtra, India. - Chincholikar, Sanjeev; Sohani, Amit (Indian Journal of Community Health, 2016)
Background: For establishing effective intervention, it is important to identify major determinants in an early stage of life. Effective prevention of adult obesity will require prevention and management of childhood obesity. Aims & Objectives: To study the epidemiological determinants of obesity in adolescent girls. Material & Methods: All adolescent school going boys and girls in the age group between 10 to 19 years were included as per definition of adolescent. 585 students were selected by systematic sample i.e. every 3rd student was included in the study sample. A pretested standardized questionnaire which consisted of questions related to sociodemographic data was used to screen the population for obesity. Results: When body mass index was correlated with various socioeconomic variables, it was found that prevalence of obesity was more in males (overweight- 20.84%;obese-5.43%) as compared to females (overweight- 16.92%; obese-3.14%),more in the upper socioeconomic status (27.27%) as compared to lower socioeconomic status(15%),more in subjects with more frequency of junk food(30.97%) as compared to having occasional junk food (20.93),more in subjects with more frequency of eating sweets ( 25.73%) as compared to occasional sweet eaters(13.59%). Conclusion: The dietary habits like more frequency of junk food, more sweet consumption, and socioeconomic status had a major impact on body mass index of children.